Primus Truber - Schoepfer der slovenischen Schriftsprache? Versuch einer Antwort unter besonderer Beruecksichtigung seines Satzbaus - Seitz, Elisabeth (Slavistische Beitraege, 1998)
The Slovenian written language begins with the works of Primus Truber, so that it must be regarded as its creation - this, in short, would be the result of 200 years of research into the beginnings of Slovenian literacy. The purpose of this work is now to create a little more clarity here and at the same time to ask the question of Primus Trüber as the creator of the Slovenian written language on a different basis than before. Another question is, how did he, when he created one, come to his Slovenian written language?